Analisis Kemampuan Representasi Matematis Pada Materi Barisan Dan Deret - Suciaty, Nella; santoso, erik; nurhikmayati, iik (Papanda Publisher, 2023)
This research aims to describe the level of ability of 32 students in class XII - MIPA 1 at SMA Negeri 1 Jatiwangi. The question instrument used in this research is 5 written test questions which refer to indicators of students' mathematical representation abilities. The data analysis technique used in this research is an interactive analysis technique which consists of three components, namely data reduction, data presentation, and drawing conclusions. The results of this research show that (1) The level of students' mathematical representation ability has an average score of 39.32 in the medium category. (2) Errors in solving statistics problems which include conceptual errors (wrong understanding of the meaning of the problem), principle errors (wrong conclusions in determining the final answer to the problem, wrong use of rules in mathematical formulas), and operational errors (wrong in using operations in mathematics such as addition, subtraction, division and multiplication). students' mathematical representations, and students' errors in solving sequences and series problems based on indicators of students' mathematical representation abilities, in class XII - MIPA 1 at SMA Negeri 1 Jatiwangi. This research uses descriptive research with a qualitative approach. The subject of this research.